(untitled) (KASBIT Business Journal, 2018)
Human Capital management is a competitive discussing term frequently used today in the brilliant minds of the entire world and globally in every organization, which plays the role of backbone for organization and makes its survival possible. In maximum productivity and success of any organization human resource management has a dominant part to play as all other organizational resources are controlled by the human. Present research reported on how well-being of the human capital impacts on the employee performance, based on the Telecom Sector firms of Pakistan with the sample employee responses. The primary data for the research is collected through questionnaires sample of 250 of the population which are based on five point Lakert scale model that has two extreme ends, strongly agree and strongly disagree. Finding of statistical analysis and literature proposes that there is extremely positive connection between employee well-being and employee performance and organizational productivity. In this study, there were four hypotheses and all of the hypotheses were accepted with the help of the obtained results and existing literature. Human capital can perform his responsibilities in a more efficient and better way if the management of a firm thinks about the better psychological well-being, working environment facility, financial and corporate social responsibilities to manage the human capital. Moreover, this also leads to lesser difficulties about health issues, punctuality and employee perseverance for the firm.